Politik Konfesionalisme Lebanon - Farhan Hibatullah (Jurnal ICMES, 2021)
This article discusses the politics of confessionalism, which has become a political choice for the religious diversity of Lebanese society. Political confessionalism is a system of government that proportionally allocates political power based on religion. The diversity of religions in Lebanon is inseparable from its complex historical journey, which then impacts social change in Lebanon. This diversity often causes various problems in Lebanon, even including armed conflict. The most significant armed conflict in Lebanon occurred in the period 1975-1990. This war is strongly influenced by religion because each actor brings their religious identity to the war. This article uses a qualitative method to explain the social changes that occurred until the Lebanese people finally agreed on the politics of confessionalism as a solution to bring socio-political stability to the country.